2006
DOI: 10.1002/chin.200638004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth, Transport, and Magnetic Properties of Ln3Co4Sn13 (Ln: La, Ce) with a Perovskite‐Like Structure.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 7 publications
10
5
0
Order By: Relevance
“…Figure 1 show the powder XRD patterns and the insets show the XRD patterns measured on the (110) surfaces at room temperature for the samples of La 3 Co 4 Sn 13 and Ce 3 Co 4 Sn 13 , which are consistent with the Yb 3 Rh 4 S n 13 -type Pm 3n space group as in previous studies [26][27][28][29][30][31]. For La 3 Co 4 Sn 13 and Ce 3 Co 4 Sn 13 sample, the Lattice parameters obtained from the XRD datas are a=9.6369 and 9.5934 Å, respectively, close to the previously reported value [4,7,12,22,[26][27][28][29][30][31], indicating the good quality of our samples.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Figure 1 show the powder XRD patterns and the insets show the XRD patterns measured on the (110) surfaces at room temperature for the samples of La 3 Co 4 Sn 13 and Ce 3 Co 4 Sn 13 , which are consistent with the Yb 3 Rh 4 S n 13 -type Pm 3n space group as in previous studies [26][27][28][29][30][31]. For La 3 Co 4 Sn 13 and Ce 3 Co 4 Sn 13 sample, the Lattice parameters obtained from the XRD datas are a=9.6369 and 9.5934 Å, respectively, close to the previously reported value [4,7,12,22,[26][27][28][29][30][31], indicating the good quality of our samples.…”
Section: Resultssupporting
confidence: 91%
“…For La 3 Co 4 Sn 13 , metallic temperature dependence is observed in the whole temperature range. A very weak kink appear near 150 K. The observations are similar to the published data in the literature [7,26]. Cheung et al suggested that T * is associated with a second-order structural transition with q=(0.5, 0.5, 0) [32].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The family of ternary stannide materials with an R 3 T 4 Sn 13 stoichiometry, where R  = La, Sr or Ca and T  = Ir, Rh or Co, have recently been studied owing to their interesting characteristics, such as superconductivity, heavy fermions, complex magnetism, electricity and thermoelectric properties78910111213141516171819202122232425. Superconducting properties of the Sr 3 Ir 4 Sn 13 (SIS) and Sr 3 Rh 4 Sn 13 (SRS) single crystals were recently observed with T C  ~ 5 K and ~4.7 K, respectively791620.…”
mentioning
confidence: 99%